A COMPARATIVE STUDY TO DETERMINE THE EFFECTIVENESS AND SAFETY OF PROBIOTICS AS AN ADJUNCT TO ANTIHISTAMINES COMPARED TO ANTIHISTAMINES ALONE IN PATIENTS WITH ALLERGIC RHINITIS - NAGUR SHARONE GRACE; MONICA N; MATTAM SARATH CHANDRA; VEENA B (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of the study are to evaluate the effectiveness and safety of probiotics as an adjunct therapy to antihistamines in comparison to antihistamines alone in individuals suffering from allergic rhinitis (AR). Methods: A non-blinded, comparative study included 100 patients with AR selected from Government E.N.T Hospital’s allergy clinic, Koti, Hyderabad. The participants were categorized into two groups of 50 patients each and received tablet levocetirizine 5 mg in the first group and tablet levocetirizine 5 mg plus capsule Sporlac plus (2.5 billion cells) in second group, for 28 days. Total nasal symptom score (TNSS), complete blood count (CBC), and absolute eosinophil count (AEC) were done at start and at the end of 28 days. Participants were followed up at the end of 28 days. Results: There were no remarkable variations observed statistically in TNSS scoring and CBC among both groups; however, clinical significance was noted within each group. Mean AEC at baseline and at the end of 28 days in group 1 was 515.8 ± 47.02 cells/μL and 325.5 ± 52.9 cells/μL and in group 2 was 504.5 ± 41.19 cells/μL and 188.3 ± 51.7 cells/μL, respectively. There was a significant variation in average AEC at the end of 28 days of treatment (p<0.05). Only mild adverse effects were observed across all groups. Conclusion: Although both treatments were found to have equal efficacy in alleviating symptoms of AR with good safety profile, probiotics as an adjunct to antihistamine significantly reduced AEC count when compared to anti-histamine alone proven to have more clinical benefit.